Knowing that You Matter, Matters! The Interplay of Meaning, Monetary Incentives, and Worker Recognition - Michael Kosfeld; Susanne Neckermann; Xiaolan Yang (Tinbergen Institute, 2014)
We manipulate workers' perceived meaning of a job in a field experiment. Half of the workers are informed that their job is important, the other half are told that their job is of no relevance. Results show that workers exert more effort when meaning is high, corroborating previous findings on the relationship between meaning and work effort. We then compare the effect of meaning to the effect of monetary incentives and of worker recognition via symbolic awards. We also look at interaction effects. While meaning outperforms monetary incentives, the latter have a robust positive effect on performance that is independent of meaning. In contrast, meaning and recognition have largely similar effects but interact negatively. Our results are in line with image-reward theory (Benabou and Tirole 2006) and suggest that meaning and worker recognition operate via the same channel, namely image seeking.
Keywords: C93; J33; M12; M52; 330; Meaning; monetary incentives; worker recognition; field experiment